Aircraft structures - Peery, David J. (Dover books on engineering., 2011)
"Still relevant 62 years after its initial publication, this legendary reference text on aircraft stress analysis is considered the best book on the subject. A knowledge of aerodynamics is a prerequisite for its discussions of basic structural theory and the application of the elementary principles of mechanics to the analysis of aircraft structures. 1950 edition"--